THE REACTIVE CAPACITY OF THE SOIL BASES OF GRAVITY-TYPE QUAY WALL - Natela Khoneliia; Svetlana Bugaeva (World Science, 2019)
The results of studies of the reactive capacity of the soil base of a gravity- type quay-wall on the basis of the method developed for calculating the “structure - soil base” system are considered. The method proposed allows determining the reactive capacity of the soil base in conditions of mixed stress state model (limit and sublimit stress state of the soil base) under and around of the base of the foundation structure in a wide range of loads of lateral earth pressure. The transformation of limit and sublimit stress state zones of the soil base on the basis of numerical modeling is presented which shows an increase of the sizes of limit stress state and a decrease of the sizes of sublimit stress state.